Tinjauan Struktur Dan Karakter Mineral Padatan Dengan Menggunakan Metode X-Ray Diffraction (XRD): Review Singkat - Prayoga, Ahmad Yudis Esa; Budiman, Christoper Michael; Intifadhah, Sahara Hamas (Progressive Physics Journal, 2025)
Indonesia is rich in various types of rocks, including igneous, sedimentary, and metamorphic rocks. Igneous and metamorphic rocks are commonly found in several regions of Indonesia, making the mineral resources of these rocks have significant potential in the country. X-ray diffraction (XRD) technique has advanced greatly in material characterization. The purpose of this research is to review various studies that discuss mineral characterization of rocks using XRD, as well as to examine different sample preparation methods, interpretation of XRD diffraction patterns, and how this technique is used to determine the mineral composition and crystallographic properties of materials in various types. The research methods used are highly varied for material processing, such as calcination, magnetic separation, slow evaporation, and grinding. The data variables obtained from this study include minerals, sample collection methods, structure, diffraction angles, composition, and their applications.